2021
DOI: 10.1177/2319714520982150
|View full text |Cite
|
Sign up to set email alerts
|

Hinduja Brothers: The Edgy Family Business at the Third Generation

Abstract: The Hinduja Group, a closely held conglomerate, is among the world’s richest and valued centurion family business. Second-generation brothers are known for fellowship, legacy and togetherness. The four brothers’ sibling partnerships worked successfully for 50 years. They see all businesses as the Hinduja family’s business and not of any individual or any individual branch’s business. The third generation holds the reins and is working closely with the fourth generation. The family has a fortune worth $11.2 bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the advent of legislative changes that discourage gender discrimination, women have made efforts to break the glass ceiling and have made their way into top-level positions in organizations. However, women’s representation in top executive positions in organizations is still limited as compared to their male counterparts (Hutchings et al, 2020; Shukla, 2021). For example, a publication by Catalyst (2020) indicated that ‘in 2019, the proportion of women in senior management roles globally grew to 29%’ but was even lower at the very top as chief executive officers’ or business heads is just 17.1%.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of legislative changes that discourage gender discrimination, women have made efforts to break the glass ceiling and have made their way into top-level positions in organizations. However, women’s representation in top executive positions in organizations is still limited as compared to their male counterparts (Hutchings et al, 2020; Shukla, 2021). For example, a publication by Catalyst (2020) indicated that ‘in 2019, the proportion of women in senior management roles globally grew to 29%’ but was even lower at the very top as chief executive officers’ or business heads is just 17.1%.…”
Section: Introductionmentioning
confidence: 99%
“…The second theme suggests the marketing behaviour themes such as customer satisfaction, word of mouth, attitude and intention (Hafiz et al, 2022). The third theme suggests emerging market topics such as economic growth (Ahuja & Pandit, 2020), microfinance (Ashta & Mor, 2022), capital structure (Pramahender, 2022), crowdfunding, firm size (Shukla, 2022) and international trade. The fourth and last theme that emerged is more (Table 2 continued) related to countries and pandemic keywords, such as Bangladesh, China, India, pandemic, COVID-19.…”
mentioning
confidence: 99%